2021
DOI: 10.1080/13625187.2021.1934440
|View full text |Cite
|
Sign up to set email alerts
|

The impact of disasters on contraception in OECD member countries: a scoping review

Abstract: Objectives: Review evidence is lacking about how contraception is affected by severe social disruption, such as that caused by the COVID-19 pandemic. The purpose of this scoping review was to explore the impact of natural and man-made disasters on contraception in OECD member countries. Methods: Manual searches and systematic searches in six electronic databases were conducted with no language restrictions. All articles were screened by at least two researchers. The data were analysed thematically. Results: 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 119 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…Evidence on the impact of critical situations or events on childbearing preferences and demand for contraception is scarce [32]. Some studies suggest that these fertility indicators PLOS GLOBAL PUBLIC HEALTH can be affected by financial hardship in the household, humanitarian crises, escalations of violence and displacement, or immediate threats to mothers or fetuses, as observed during the Zika epidemic [32][33][34][35]. Besides acute crises, studies conducted in various African settings have also noted that uncertainty and fear are driving factors of postponing or avoiding a pregnancy [34,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on the impact of critical situations or events on childbearing preferences and demand for contraception is scarce [32]. Some studies suggest that these fertility indicators PLOS GLOBAL PUBLIC HEALTH can be affected by financial hardship in the household, humanitarian crises, escalations of violence and displacement, or immediate threats to mothers or fetuses, as observed during the Zika epidemic [32][33][34][35]. Besides acute crises, studies conducted in various African settings have also noted that uncertainty and fear are driving factors of postponing or avoiding a pregnancy [34,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have provided evidence of the long-lasting negative psychological impact of this disaster, manifested as depressive symptoms and anxiety not only among the victims’ families and community residents, but also in the Korean population as a whole [ 22 , 23 , 24 , 25 ]. Previous studies have reported that social disasters affect contraceptive behavior, and that depressive symptoms may affect methods of contraception [ 26 , 27 ]. In addition, a recent study reported that social disasters significantly reduce the fertility rate for a fairly long period of time [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accord with reviews conducted by Freed et al , stating various negative effects. [ 53 ] It is important to point out that the review had a similar methodology and scanned similar electronic databases. The objective is similar but narrower in terms of the type of natural calamity focused.…”
Section: Discussionmentioning
confidence: 99%